Pengaruh Ojek Online: Faktor Faktor Yang Mempengaruhi Pendapatan Driver Gojek Dan Grab di Kota Yogyakarta Tahun 2023 Dengan Metode Kualitatif - Muhammad Naufal Dani Oktavian; Prasanti Tika Pertiwi; Ria Agem Safitri; Stevia Cahya Hediana (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2023)
The effect of working hours, passenger targets, driver age, and fuel consumption on the income of Gojek and Grab drivers in Yogyakarta City. This study aims to determine the effect of the above variables on the income of Gojek and Grab drivers. The purpose of this research is expected to be useful and add insight for readers, besides that it can be a source of information about the factors that influence the income of Gojek and Grab drivers. In the research we conducted, the method we used was quantitative method. The data source used in this study is primary data obtained from the results of questionnaires distributed to Gojek and Grab drivers in Yogyakarta City. In this type of research using qualitative research using the classical assumption test in data processing. Driver working hours have a significant effect on income because the relationship between working hours and driver income has a significant positive relationship. Passenger targets do not have a significant influence on driver income. Driver age has a significant influence on driver income. Gasoline needs do not have a significant influence on the income of online motorcycle taxi drivers in Yogyakarta City. From the results of the analysis with the classical assumption test above, it can be concluded that working hours and driver age have a significant influence on the income of online ojek drivers. This is evidenced by the results of the classical assumption test conducted and produces a value that is in accordance with the requirements.